BNT-doped high-power ternary lead-based PMnS-PZT piezoelectric ceramic material and preparation method thereof

The BNT-doped PMnS-PZT piezoelectric ceramic material addresses the limitations of existing materials by enhancing piezoelectric performance and temperature stability through optimized composition and processing, achieving superior mechanical quality and dielectric properties for high-power applications.

CN119156116AInactive Publication Date: 2024-12-17SHANDONG LIANS INTELLIGENT TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411648149.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing piezoelectric ceramic materials face challenges in achieving high piezoelectric performance, mechanical quality factor, and temperature stability, particularly in high-power applications such as piezoelectric underwater acoustic transducers and transformers.

Method used

A BNT-doped high-power ternary lead-based PMnS-PZT piezoelectric ceramic material is developed by adjusting the proportions of BNT, PMnS, and PZT, with specific ratios of BNT to PMnS-PZT (0.02≤x≤0.04) and PMnS to PZT (0.05≤y≤0.07), using a solid phase reaction method involving mixing, ball-milling, sieving, granulating, and sintering processes to enhance piezoelectric properties.

Benefits of technology

The ceramic material exhibits improved piezoelectric coefficient (324~384 pC/N), mechanical quality factor (1411~1680), and temperature stability (8.8% strain change in 20~200°C), with low dielectric loss (0.30%~0.39%) and high dielectric constant (1544~1987) while maintaining cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156116A_ABST
    Figure CN119156116A_ABST
Patent Text Reader

Abstract

The invention discloses a BNT doped high-power ternary lead-based PMnS-PZT piezoelectric ceramic material and a preparation method thereof, the piezoelectric ceramic material is a solid solution of BNT and PMnS-PZT, and the PMnS-PZT is a solid solution of PMnS and PZT. The room temperature dielectric constant of the piezoelectric ceramic material is 1544-1987, the room temperature dielectric loss is 0.30%-0.39%, the maximum polarization intensity is about 30.20-36.32 [mu] C / cm < 2 >, the strain value under an electric field of 5 kV / mm is about 0.177%-0.233%, the piezoelectric coefficient is about 324-384 pC / N, the planar electromechanical coupling coefficient is 0.608-0.633, and the mechanical quality factor is 1411-1680. The strain change rate of the strain value of the piezoelectric ceramic material in the temperature range of 20-200 DEG C is 8.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of piezoelectric ceramics, and in particular relates to a BNT-doped high-power ternary lead-based PMnS-PZT piezoelectric ceramic material and a preparation method thereof. Background Art

[0002] Over the years, piezoelectric ceramic materials have been widely used in electromechanical components due to their unique properties, namely the mutual conversion of electrical energy and mechanical energy, and are an indispensable foundation for the development of science and technology today. Compared with traditional electromagnetic materials, piezoelectric ceramic materials have the advantages of high sensitivity, good accuracy, fast response speed, miniaturization and strong scalability. Typical applications include underwater transducers, ultrasonic welders, autofocus modules in digital cameras, and positioning devices in high-precision equipment.

[0003] Different piezoelectric devices have different piezoelectric performance requirements for piezoelectric ceramics. According to the operating frequency, piezoelectric applications can be divided into two categories: resonant and non-resonant. The resonant displacement is determined by the piezoelectric coefficient d 33 and mechanical quality factor Q m Therefore, for resonant piezoelectric devices such as high-power piezoelectric underwater acoustic transducers and transformers, high levels of d 33 and Q m However, they are almost inversely proportional, developing both d 33 and Q m The development of piezoelectric ceramic materials remains challenging.

[0004] Soft PZT ceramics (PZT-5) have relatively high d 33 , but its Q m The hard PZT (PZT-8) is the opposite; the commercial PZT-4 ceramic d 33 and Q m The piezoelectric coefficient and mechanical quality factor are still not high enough. d 33 ≈300 pC / N, Q m ≈500). Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a BNT-doped high-power ternary lead-based PMnS-PZT piezoelectric ceramic material, which utilizes Bi (Ni1 / 2 Ti 1 / 2 )O3 (BNT for short) for high power ternary lead-based Pb(Mn 1 / 3Sb 2 / 3 )O3-Pb(Zr 0.48 Ti 0.52 )O3 (PMnS-PZT for short) is doped, and the piezoelectric properties of the piezoelectric ceramic material are adjusted by changing the different proportions of the three components (BNT, PMnS and PZT).

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned BNT-doped high-power ternary lead-based PMnS-PZT piezoelectric ceramic material. The piezoelectric ceramic material obtained by this preparation method effectively solves the technical problem that existing piezoelectric ceramic materials are difficult to have both high piezoelectric performance, mechanical quality factor and good temperature stability.

[0007] The purpose of the present invention is achieved through the following technical solutions.

[0008] A BNT-doped high-power ternary lead-based PMnS-PZT piezoelectric ceramic material is a solid solution of BNT and PMnS-PZT, wherein the ratio of BNT to PMnS-PZT is: x :(1- x ), 0.02≤x≤0.04; PMnS-PZT is a solid solution of PMnS and PZT. According to the amount of substance, the ratio of PMnS to PZT in PMnS-PZT is y :(1- y ), 0.05≤ y ≤0.07, BNT is Bi(Ni 1 / 2 Ti 1 / 2 )O3, PMnS is Pb(Mn 1 / 3 Sb 2 / 3 )O3, PZT is Pb(Zr 0.48 Ti 0.52 )O3.

[0009] The method for preparing the piezoelectric ceramic material comprises the following steps: Step 1), mixing a Pb source, a Mn source, a Sb source, a Zr source, a Ti source, a Bi source and a Ni source to obtain a mixed raw material, ball-milling the mixed raw material, sieving, and pre-calcining at 850-950° C. for 2-4 hours to obtain a pre-sintered powder, wherein, by amount of substance, the ratio of Pb in the Pb source, Mn in the Mn source, Sb in the Sb source, Zr in the Zr source, Ti in the Ti source, Bi in the Bi source and Ni in the Ni source is (1- x ): : :0.48(1- y)(1- x ): : x : ; In step 1), the Pb source is Pb3O4, the Mn source is MnCO3, the Sb source is Sb2O3, the Zr source is ZrO2, the Ti source is TiO2, the Bi source is Bi2O3, and the Ni source is Ni2O3.

[0010] Step 2), ball-milling the pre-sintered powder for a second time, and sieving to obtain a second ball-milled powder; In step 1) and step 2), the ball milling time is 20 to 30 hours, and the ball milling speed is 350 to 450 r / min.

[0011] In step 1) and step 2), the ball milling includes wet ball milling and drying performed sequentially, the drying temperature is 60-80° C., and the drying time is 4-6 hours.

[0012] Step 3), granulating the secondary ball-milled powder, sieving, and tableting to obtain ceramic green sheets; In step 3), the granulation binder is a polyvinyl alcohol aqueous solution, and the concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 5-8wt%.

[0013] In the above technical solution, the polyvinyl alcohol aqueous solution is 1-5wt% of the secondary ball-milled powder.

[0014] In step 3), the ceramic green sheet has a diameter of 8-10 mm and a thickness of 0.8-1 mm.

[0015] In step 3), the tableting pressure is 6-8 MPa, and the tableting time is 3-5 min.

[0016] In step 1), step 2) and step 3), the aperture of the sieve is 60-80 mesh.

[0017] Step 4), debinding the ceramic green sheet, sintering at 1200-1250° C. for 1-3 hours to obtain a piezoelectric ceramic sheet, and coating the piezoelectric ceramic sheet with electrodes, sintering the electrodes, and polarizing in silicone oil to obtain a piezoelectric ceramic material.

[0018] In step 4), the debinding temperature is 800-850° C., and the debinding time is 2-4 hours.

[0019] In step 4), coating the electrodes is to coat the piezoelectric ceramic sheet with electrodes on both sides, and the electrodes are high-temperature silver paste.

[0020] In step 4), the heating rate of the electrode sintering is 2-5°C / min.

[0021] In step 4), the electrode sintering temperature is 600-650° C., and the electrode sintering time is 20-40 minutes.

[0022] In step 4), the polarization temperature in the silicone oil is 120-140° C., the polarization field intensity in the silicone oil is 3-4 kV / mm, and the polarization time in the silicone oil is 30-60 minutes.

[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. The piezoelectric ceramic material of the present invention uses BNT as the third element solid solution, which plays the role of soft doping and hard doping. By introducing the third element solid solution BNT, the piezoelectric coefficient and mechanical quality factor of the piezoelectric ceramic material of the present invention are improved, and a high level of d 33 and Q m The piezoelectric ceramic material of the present invention has excellent piezoelectric performance, low loss and good mechanical quality factor.

[0024] 2. The room temperature dielectric constant of the piezoelectric ceramic material prepared by the present invention is 1544~1987, the room temperature dielectric loss is 0.30%~0.39%, and the maximum polarization strength is about 30.20~36.32μC / cm 2 , the strain value under the electric field of 5 kV / mm is about 0.177%~0.233%, the piezoelectric coefficient is about 324~384pC / N, the plane electromechanical coupling coefficient is 0.608~0.633, and the mechanical quality factor is 1411~1680. The strain change rate of the piezoelectric ceramic material of the present invention in the temperature range of 20~200℃ is 8.8%.

[0025] 3. The temperature stability of the piezoelectric ceramic material of the present invention is improved compared with other lead-based piezoelectric ceramics.

[0026] 4. The preparation method of the present invention adopts a traditional solid phase reaction method, which is simple to operate and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 XRD of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3; Figure 2 (a) XRD and (b) phase content of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5; Figure 3 (a-e) cross-sectional SEM and (f) average grain size of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3; Figure 4 The cross-sectional SEM of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5; Figure 5 are dielectric constant and dielectric loss, wherein (a) is the piezoelectric ceramic material prepared in Examples 1-2 and Comparative Examples 1-3, and (b) is the piezoelectric ceramic material prepared in Examples 2-3 and Comparative Examples 4-5; Figure 6 are hysteresis loops of piezoelectric ceramic materials, wherein (a) is the hysteresis loop of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3, and (b) is the hysteresis loop of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5; Figure 7 are bipolar strain curves of piezoelectric ceramic materials, wherein (a) is the bipolar strain curve of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3, and (b) is the bipolar strain curve of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5; Figure 8 are piezoelectric performance change curves of piezoelectric ceramic materials, wherein (a) is a piezoelectric performance change curve of the piezoelectric ceramic materials prepared by Examples 1 to 2 and Comparative Examples 1 to 3, and (b) is a piezoelectric performance change curve of the piezoelectric ceramic materials prepared by Examples 2 to 3 and Comparative Examples 4 to 5; Fig. 9 The piezoelectric coefficient of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3 varies with temperature; Fig.10 (a) Unipolar strain curve and (b) piezoelectric performance temperature curve of the piezoelectric ceramic material prepared in Example 3 at different temperatures. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0029] In the following examples, the Pb source is Pb3O4, the Mn source is MnCO3, the Sb source is Sb2O3, the Zr source is ZrO2, the Ti source is TiO2, the Bi source is Bi2O3, and the Ni source is Ni2O3, wherein Pb3O4, MnCO3, Sb2O3, ZrO2, TiO2, Bi2O3 and Ni2O3 are all powders purchased from Shanghai MacLean Reagent Co., Ltd.

[0030] In the following examples, the dielectric constant and dielectric loss were measured at a frequency of 1 kHz.

[0031] In the following examples, the hysteresis loops were measured at an electric field of 5 kV / mm and a frequency of 1 Hz.

[0032] In the following examples, the bipolar strain curves were measured under an electric field of 5 kV / mm. Examples 1 to 3 and Comparative Examples 1 to 5

[0033] A method for preparing a piezoelectric ceramic material comprises the following steps: Step 1), Pb source, Mn source, Sb source, Zr source, Ti source, Bi source and Ni source are mixed to obtain a mixed raw material, ethanol and ball milling beads (zirconia balls) are added to the mixed raw material, the mass ratio of ball milling beads, mixed raw material and ethanol is 2:1:1, wet ball milling is performed at 350 r / min for 20 hours, and after ball milling, it is dried at T℃ for 6 hours, sieved (mesh size is M), and pre-calcined at 850℃ for 3 hours to obtain a pre-sintered powder, wherein, in terms of the amount of substance, the ratio of Pb in the Pb source, Mn in the Mn source, Sb in the Sb source, Zr in the Zr source, Ti in the Ti source, Bi in the Bi source and Ni in the Ni source is (1-x): : :0.48(1-y)(1-x): :x: ; Step 2), the pre-sintered powder is subjected to secondary ball milling: ethanol and ball milling beads (zirconia balls) are added to the pre-sintered powder, the mass ratio of the ball milling beads, the pre-sintered powder and the ethanol in step 2) is 2:1:1, wet ball milling is performed at 350 r / min for 20 hours, and after ball milling, it is dried at T℃ for 5 hours and sieved (mesh size is M) to obtain secondary ball milled powder; Step 3), the secondary ball-milled powder is granulated with a binder, sieved (mesh size is M), and pressed at a pressure of 6 MPa for 3 minutes to obtain a ceramic green sheet with a diameter of 10 mm and a thickness of 1 mm, wherein the binder is a polyvinyl alcohol aqueous solution, the concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is Awt%, and the polyvinyl alcohol aqueous solution is Zwt% of the secondary ball-milled powder.

[0034] Step 4), heating the ceramic green sheet to 800°C at a heating rate of 5°C / min and debinding at 800°C for 4 hours, heating the green sheet to 1200°C at a heating rate of 2°C / min after debinding and sintering at 1200°C for 2 hours to obtain a piezoelectric ceramic sheet, coating the piezoelectric ceramic sheet with electrodes, sintering the electrodes and polarizing in silicone oil to obtain a piezoelectric ceramic material, wherein coating the electrodes is to coat the piezoelectric ceramic sheet with high-temperature silver paste on both sides, sintering the electrodes is to heat the temperature to 600°C at a heating rate of 5°C / min and sintering the electrodes at 600°C for 30 minutes, the polarization temperature in the silicone oil is 120°C, the polarization field strength in the silicone oil is 3kV / mm, and the polarization time in the silicone oil is 30 minutes.

[0035] The x, y, T, M, A and Z of the piezoelectric ceramic materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.

[0036] Table 1

[0037] Figure 1 The XRD patterns of the piezoelectric ceramic materials prepared in Examples 1 to 2 and Comparative Examples 1 to 3 are shown in Table 1. The piezoelectric ceramic materials prepared in Example 1 and Comparative Example 1 exhibit a single perovskite structure without any other impurities. The XRD patterns of the piezoelectric ceramic materials prepared in Example 2 and Comparative Examples 2 to 3 show a single perovskite structure without any other impurities. o The generation of bismuth titanate (Bi2Ti2O7) secondary phase was observed near the diffraction peak, which may be due to the chemical reaction between excessive bismuth oxide (Bi2O3) and titanium dioxide (TiO2) doped with BNT. With the increase of BNT doping amount, the diffraction peak intensity of Bi2Ti2O7 increases to a certain extent.

[0038] from Figure 1 Center right 43 o ~46 o From the enlarged view of the diffraction peak, it can be seen that with the increase of BNT doping amount, the diffraction peak tends to shift to the left. 3+ (103 pm) usually replaces Pb at A position 2+ ions (77.5 pm), creating lead ion vacancies to maintain the electrical neutrality of the unit cell and increase the unit cell volume. 3+ (56~60 pm) replaces Ti at the B site which is closer to its radius 4+ (60.5pm) ions, generating oxygen ion vacancies causing the unit cell volume to shrink. The left shift of the diffraction peak is due to the higher proportion of Bi 3+ The unit cell expansion caused by Ni 3+ The degree of unit cell shrinkage caused by this.

[0039] Figure 2 (a) is the XRD spectrum of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5, Figure 2 (b) is the phase content of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5, Figure 2 It can be seen that the phase structure of ceramics is a single perovskite structure. Figure 2 42~47 on the right side of (a) o From the enlarged view of the diffraction peak near the PMnS, it can be observed that with the increase of PMnS content, an obvious phase transition occurs, that is, the change process from tetragonal phase to coexistence structure of tetragonal phase and rhombohedral phase, and then to rhombohedral phase. The phase contents of each phase of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5 are as follows: Figure 2As shown in (b), the phase structure of the piezoelectric ceramic materials prepared in Example 2 and Example 3 is located in the morphotropic phase boundary (MPB), indicating that increasing the content of PMnS can induce the phase structure to transform from a tetragonal phase to a rhombohedral phase, and it is expected to obtain higher electromechanical properties in the process.

[0040] Figure 3 The cross-sectional SEM images and average grain size variation graphs of the piezoelectric ceramic materials prepared in Example 1, Example 2 and Comparative Examples 1 to 3, wherein (a) is a cross-sectional SEM image of the piezoelectric ceramic material prepared in Comparative Example 1, (b) is a cross-sectional SEM image of the piezoelectric ceramic material prepared in Example 1, (c) is a cross-sectional SEM image of the piezoelectric ceramic material prepared in Example 2, (d) is a cross-sectional SEM image of the piezoelectric ceramic material prepared in Comparative Example 2, (e) is a cross-sectional SEM image of the piezoelectric ceramic material prepared in Comparative Example 3, and (f) is a graph showing the average grain size variation. Figure 3 From (a), (b) and (c), it can be seen that the ceramic grains of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Example 1 are tightly bound, have low porosity, and are mostly polyhedral in shape. Figure 3 As shown in (d) and (e), the grain boundaries of the piezoelectric ceramic materials prepared in Comparative Examples 2-3 tend to be smooth and have more pores. The average grain size of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 2-3 is as follows: Figure 3 (f).

[0041] Figure 4 The cross-sectional SEM images of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5, wherein (a) is the cross-sectional SEM image of the piezoelectric ceramic material prepared in Comparative Example 4, (b) is the cross-sectional SEM image of the piezoelectric ceramic material prepared in Example 2, (c) is the cross-sectional SEM image of the piezoelectric ceramic material prepared in Example 3, and (d) is the cross-sectional SEM image of the piezoelectric ceramic material prepared in Comparative Example 5. The grain size is very sensitive to the change in the content of PMnS. As the content of PMnS increases, the average grain size (ACS) gradually decreases from 4.3μm to 1.8μm. From the cross-sectional SEM image of the piezoelectric ceramic material, it can be seen that the main fracture mode is intergranular fracture. The microscopic morphology of the piezoelectric ceramic material prepared in Example 3 is dense and uniform, indicating that it may have good comprehensive performance, which is of great significance for the application of high-power devices.

[0042] The dielectric properties (dielectric constant ε r,RT and dielectric loss tanδ) and resonant frequency (maximum polarizability P max ), and calculated its mechanical quality factor Q m and electromechanical coupling coefficient kp ; The hysteresis loop and bipolar strain curve of the piezoelectric ceramic material were tested by a ferroelectric tester, and the maximum strain value S pos ; Using quasi-static d 33 The tester tests the piezoelectric coefficient of ceramic materials d 33 The results are shown in Table 2 and Figures 5 to 8 shown.

[0043] Table 2

[0044] Figure 5 (a) is the dielectric constant and dielectric loss of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3. Figure 5 As shown in (a), the piezoelectric ceramic material prepared in Example 2 has the best dielectric properties, and the dielectric constant ε r, RT The dielectric loss tanδ is 1612 and 0.36% respectively. 3+ When it enters PMnS-PZT, it usually occupies the A-site lattice. Due to the imbalance of electric charges, excess positive charge will appear in the unit cell, that is, Pb 2+ Vacancies make it easier for the domain wall to move, which increases the dielectric constant and dielectric loss. 3+ After entering the B-site lattice, O will be generated 2- The vacancy causes the unit cell to shrink. 2- When vacancies diffuse to the domain wall, they tend to "pin" the domain wall, hindering the movement of the domain wall and making it difficult for the ferroelectric domain to fully turn during the polarization process. 2+ When the concentration of donor doping caused by vacancies is low, most of the acceptor energy levels are compensated by the electrons of the donor energy levels, so that the conductivity of the ceramic becomes lower. Therefore, the dielectric loss of the piezoelectric ceramic material prepared in Example 2 is also relatively low. Figure 5 (b) is the dielectric constant and dielectric loss of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5. The piezoelectric ceramic material prepared in Example 3 has the highest dielectric constant ε r, RT This is mainly because the physical phase of the piezoelectric ceramic material is near the quasi-isotropic phase boundary at this time, which is conducive to the steering of spontaneous polarization, that is, it is conducive to the relative displacement between titanium ions and oxygen ions, and the piezoelectric ceramic material prepared in Example 3 has a dense microstructure and uniform grain development.

[0045] Figure 6 (a) is the hysteresis loop of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3. Figure 6 As can be seen from (a), the piezoelectric ceramic material prepared in Example 2 P max36.2 μC / cm 2 , which is related to the higher rhombohedral phase content of the piezoelectric ceramic material. Figure 6 (b) is the hysteresis loop of the piezoelectric ceramic material prepared in Examples 2-3 and Comparative Examples 4-5, Figure 6 As shown in (b), the piezoelectric ceramic material prepared in Comparative Example 5 P max Maximum, 40.82 μC / cm 2 , which can be attributed to the high rhombohedral phase content of the piezoelectric ceramic material.

[0046] Figure 7 (a) is the bipolar strain curve of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3. Figure 7 (b) is the bipolar strain curve of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5. Figure 7 As shown in (b), the piezoelectric ceramic material prepared in Example 3 has the maximum strain of about 0.233%. This is mainly due to the improvement of polarization and domain wall mobility by the coexistence of multiple phases near the morphotropic phase boundary (MPB) region.

[0047] Figure 8 (a) is the piezoelectric performance curves of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3. Figure 8 (b) is the piezoelectric performance curves of the piezoelectric ceramic materials prepared in Examples 2-3 and Comparative Examples 4-5. Figure 8 It can be seen that the piezoelectric ceramic material prepared in Example 3 d 33 and k p Both reached their maximum values, which were 384 pC / N and 0.633 respectively.

[0048] Fig. 9 The piezoelectric coefficient temperature variation curves of the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3. Fig. 9 It can be seen that at room temperature to 350 o Within the temperature range of 150°C, the piezoelectric ceramic materials prepared in Examples 1-2 and Comparative Examples 1-3 o Before C d 33 It basically maintains above 87% of the room temperature level, showing good temperature stability and can meet the requirements of high-power piezoelectric applications.

[0049] Fig.10(a) is the unipolar strain curve of the piezoelectric ceramic material prepared in Example 3 at different temperatures. In the temperature range of 25 to 200°C and under an applied electric field of 3 kV / mm, the strain change rate of the piezoelectric ceramic material prepared in Example 3 is only 8.8%. Fig.10 (a) The maximum strain value S in the monopolar strain curve obtained pos and the maximum electric field strength of the test monopolar strain curve E max The calculated inverse piezoelectric coefficient d 33 * ( S pos / E max ) is in the range of 766 ~ 868 pm / V, indicating that the piezoelectric ceramic material prepared in Example 3 has excellent temperature stability. Fig.10 (b) is the piezoelectric performance temperature curve of the piezoelectric ceramic material prepared in Example 3 at different temperatures. It is found that the piezoelectric ceramic material prepared in Example 3 d 33 and Q m In 175 o C remained essentially unchanged even in 280 o C high temperature, the piezoelectric ceramic material prepared in Example 3 d 33 and Q m It can still maintain about 80% of the maximum value.

[0050] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A BNT-doped high-power ternary lead-based PMnS-PZT piezoelectric ceramic material, characterized in that: It is a solid solution of BNT and PMnS-PZT, wherein the ratio of BNT to PMnS-PZT is x :(1- x ), 0.02≤x≤0.04; PMnS-PZT is a solid solution of PMnS and PZT. According to the amount of substance, the ratio of PMnS to PZT in PMnS-PZT is y :(1- y ), 0.05≤ y ≤0.07, BNT is Bi(Ni 1 / 2 Ti 1 / 2 )O3, PMnS is Pb(Mn 1 / 3 Sb 2 / 3 )O3, PZT is Pb(Zr 0.48 Ti 0.52 )O3.

2. The method for preparing a piezoelectric ceramic material according to claim 1, characterized in that: The following steps are involved: Step 1), Pb source, Mn source, Sb source, Zr source, Ti source, Bi source and Ni source are mixed to obtain a mixed raw material, the mixed raw material is ball-milled, sieved, and pre-sintered at 850-950° C. for 2-4 hours to obtain a pre-sintered powder, wherein, by amount of substance, the ratio of Pb in the Pb source, Mn in the Mn source, Sb in the Sb source, Zr in the Zr source, Ti in the Ti source, Bi in the Bi source and Ni in the Ni source is (1-x): : : 0.48(1-y)(1-x): :x: ; Step 2), ball-milling the pre-sintered powder for a second time, and sieving to obtain a second ball-milled powder; Step 3), granulating the secondary ball-milled powder, sieving, and tableting to obtain ceramic green sheets; Step 4), debinding the ceramic green sheet, sintering at 1200-1250° C. for 1-3 hours to obtain a piezoelectric ceramic sheet, and coating the piezoelectric ceramic sheet with electrodes, sintering the electrodes, and polarizing in silicone oil to obtain a piezoelectric ceramic material.

3. The preparation method according to claim 2, characterized in that: In step 4), the debinding temperature is 800-850° C., and the debinding time is 2-4 hours.

4. The preparation method according to claim 2, characterized in that: In step 4), the electrode sintering temperature is 600-650° C., and the electrode sintering time is 20-40 minutes.

5. The preparation method according to claim 2, characterized in that: In step 4), the polarization temperature in the silicone oil is 120-140° C., the polarization field intensity in the silicone oil is 3-4 kV / mm, and the polarization time in the silicone oil is 30-60 minutes.

6. The preparation method according to claim 2, characterized in that: In step 3), the granulation binder is a polyvinyl alcohol aqueous solution, and the concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 5-8wt%.

7. The preparation method according to claim 6, characterized in that: The polyvinyl alcohol aqueous solution is 1-5 wt % of the secondary ball-milled powder.

8. The preparation method according to claim 2, characterized in that: In step 3), the ceramic green sheet has a diameter of 8-10 mm and a thickness of 0.8-1 mm.

9. The preparation method according to claim 2, characterized in that: In step 3), the tableting pressure is 6-8 MPa, and the tableting time is 3-5 min.

10. The preparation method according to claim 2, characterized in that: The sieve mesh size is 60-80 mesh.

Citation Information

Patent Citations

  • Cerium-manganese co-doped lead zirconate titanate-based piezoelectric ceramic material and preparation method thereof

    CN117326866A

  • Piezoelectric actuators and method of making same

    US6231779B1